Vitamin C oxidation in a Rushton tank: an experimental study (Revista Científica Integrada, 2025)
Objective: To quantify the oxidation of vitamin C in a Rushton tank as a function of time, presence of baffles, rotation, and type of impellers. Method: Experimental study, of the clinical trial type, which used iodometric analysis to quantify the mass of vitamin C in two presentations: effervescent tablet (Cebion®), and pure ascorbic acid capsule. Two 1L solutions of vitamin C were prepared and subjected to rotation of 0, 200, 400, and 600 rpm, with and without the presence of baffles and with an axial or radial impeller. Results: A higher percentage of loss was observed in the experiments with Cebion® compared to pure vitamin C. Furthermore, in both experiments, the highest loss rate was at a rotation of 600 rpm and with the use of a radial impeller. Conclusion: This study broadens the understanding of ascorbic acid oxidation and suggests further research exploring other presentations of vitamin C, considering reducing factors and quantitative variations.
Keywords: Ascorbic acid; Vitamin c; oxidation; Rushton tank; Degradation